Procurement Management Analysis of Goods/Service Provincial Government of Central Sulawesi - Bakarbessy, Maria Lea Frensy; M, Rudin; Assah, Denih (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2025)
The objective of this research is to investigate and assess how the principles of procurement for goods and services are put into practice in the Government of the Central Sulawesi Province. Through a qualitative research methodology, information was gathered from observation, interviews, and documentation with four chosen participants. The analysis was carried out in five distinct phases: data collection, data simplification, data demonstration, validation, and final thoughts. The evaluation of procurement principles is based on the criteria specified in Presidential Regulation No. 21 of 2021. The findings reveal that the core procurement principles such as transparency, accountability, openness, competition, and fairness, have not been fully implemented. Supporting factors include adequate facilities that comply with national procurement standards and a well-structured training model aligned with institutional needs. However, several challenges persist, including technical issues during tender announcements due to server disruptions, low participation rates during the registration phase, and limited responsiveness and personnel shortages during the job explanation stage. These findings highlight the need for improved infrastructure and administrative capacity to ensure effective and compliant procurement processes.